2008
DOI: 10.1111/j.1365-2648.2008.04758.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, attrition and transition into nursing

Abstract: Further national and international research is needed to understand better the causal variables underpinning differential attrition rates, with particular regard to understanding how different groups may experience the relationship between education and their broader circumstances and between the theoretical and the clinical elements of nurse education itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 16 publications
1
61
1
Order By: Relevance
“…Th e number of students who do not end up enrolled nursing studies ranged up to 30% 1 . Th e most common reasons for non-completion of the study are a failure during the study, personal and family reasons, wrong choice of career, unrealized expectations about the study, and nursing and fi nancial diffi culties 2,3 . It is expected that nurses during education acquire the necessary knowledge, skills and attitudes, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Th e number of students who do not end up enrolled nursing studies ranged up to 30% 1 . Th e most common reasons for non-completion of the study are a failure during the study, personal and family reasons, wrong choice of career, unrealized expectations about the study, and nursing and fi nancial diffi culties 2,3 . It is expected that nurses during education acquire the necessary knowledge, skills and attitudes, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…nurses), variable age is positively cor related with the results achieved during studies. 13,[32][33][34][39][40][41][42] Generally, in case of older students, significantly better results of learning are noted as opposed to students who began their studies under the age of 26, regard less of any additional qualifications on entry. 32,40 In the studies on the reasons of attrition at the nursing depart ment, it was the young age that was pointed to as a negative predictor.…”
Section: Discussionmentioning
confidence: 99%
“…31 Also, in case of a highly feminised profession such as nursing, it was observed that men bear a sig nificantly higher risk of dropping out than women. 13,[32][33][34] On the other hand, studies performed among the participants of a military medical programme show that it is women who present a greater attrition risk than men (OR=2.4). Also, when learning at a dental school, a tendency is observed among men to achieve higher scores in the practical tests and better grade averages, however, there is no data on the subject of risk evalua tion in this field of studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is diffi cult to assess what the picture of attrition for BME nursing students might be nationally because data by ethnicity was not reported. Despite sustained political, professional, and educational concern attrition rates on a national scale vary as much as 5% to 50% (Mulholland, Anionwu, Atkins, Tappern, & Franks, 2008).…”
Section: Bme Student Successmentioning
confidence: 99%